The idea of palliative and hospice care: a historical overview - Kowalik, Grażyna (Medical Studies/Studia Medyczne, 2013)
In face of the final phase of a terminal disease, the patient’s family is always in a difficult position. A progressing chronic disease (especially cancer) of one of the family members directly influences the mental and physical state of their closest of kin. Hospice care helps the dying patients and their families. The term “hospitium” is connected through classical Latin to the word “hospes”, which means a person connected with another in a lasting relationship arising out of hospitality, (a host) taking care of newcomers, a traveller, or one visiting a road house. Whereas the concept of palliative care was derived from the following English words: palliate – to relieve pain; palliation – making the symptoms of a disease less severe without curing it. The hospice movement has a very long history, and reaches back to pagan traditions. Initially care was provided in shelters, asylums for the poor and inns. In France, a hospice (asylum) founded in the 15th century for the care over the poorest stands to this day. A great change in the history of nursing was initiated in the 19th century. It was a time of intensive development for medicine and discoveries in the field of biology. Palliative and hospice care as well as palliative medicine owe their professional origins to C. Sanders, the founder of St Christopher’s Hospice in London in 1967. It is also known that in 1987, a palliative care ward began its functioning in Montreal. In Poland, the need to organise household care over seriously ill patients was noticed by H. Chrzanowska (1964), who is seen as the precursor of this kind of care. In the 1980s and 1990s, the idea of hospices experienced a real boom in Poland. Currently a hospice stands for a centre of care over patients in their so-called terminal phase of the disease, where interdisciplinary care is provided. This care creates the conditions for a dignified life until the very end, and thus suffering, pain and death are no longer a problem of the patient alone.